2021
DOI: 10.1016/j.parkreldis.2020.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between retinal nerve fiber layer thickness and cognitive progression in Parkinson's disease: A longitudinal study

Abstract: Background: Retinal abnormalities measured by optical coherence tomography (OCT) have been detected in both Parkinson's disease (PD) and Alzheimer's disease (AD). Cognitive impairment is not only found in AD, but 75-90% of PD patients will also develop dementia in the late stage of disease. We assessed whether baseline retinal nerve fiber layer (RNFL) thickness predicted worsening of cognitive status over time and the correlation between RNFL thickness and the detailed impaired cognitive domains in PD. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Mitochondrial dysfunction in PD patients, such as mitochondrial DNA mutations and deletions, will severely affect the retinal oxygen supply [14] . The above pathological process will damage the optic nerve, resulting in a reduced ability of the optic nerve to transmit visual information to the brain, and this upstream nerve damage will exacerbate the progression of PD [15] . As a non-invasive imaging technique, OCTA can rapidly measure and analyze pRNFL thickness and blood flow to evaluate the degree of optic disc neurofibrillary cell loss and vascular degeneration in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction in PD patients, such as mitochondrial DNA mutations and deletions, will severely affect the retinal oxygen supply [14] . The above pathological process will damage the optic nerve, resulting in a reduced ability of the optic nerve to transmit visual information to the brain, and this upstream nerve damage will exacerbate the progression of PD [15] . As a non-invasive imaging technique, OCTA can rapidly measure and analyze pRNFL thickness and blood flow to evaluate the degree of optic disc neurofibrillary cell loss and vascular degeneration in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, retinal abnormalities as measured by optical coherence tomography (OCT) appear to be promising in PDD. Studies have shown a correlation between retinal nerve fiber layer thickness or macular ganglion cell-inner plexiform layer complex thickness and cognitive dysfunction implying that OCT may be useful for predicting cognitive dysfunction in PD patients [71,72].…”
Section: Biomarkers In Pdd and Dlbmentioning
confidence: 99%
“…The validation strategies used for clinical scales and questionnaires, where a new instrument must correlate with another already-validated measure, may not be sufficient for the validation of AI-generated outputs. While recognizing that the use of a “biomarker” identified from a population might not be appropriate for application to an individual [ 8 ], researchers may still need to compare AI outputs with those of established techniques such as quantitative MRI/SPECT [ 9 ], corneal confocal microscopy [ 10 ], camera tremor magnification [ 11 ], and retinal nerve fiber layer thickness [ 12 ].…”
Section: Validationmentioning
confidence: 99%